ANNUAL FESTIVALS AND FIVE-YEAR OF CANDELARIA VIRGIN OF THE SORROW IN HUANCHACO: RELIGIOUS EXPRESSION OF FISHERMEN OF THE NORTH COAST OF PERU - Prieto, Oscar Gabriel (2011)
In this article, I will study two traditional and modern catholic festivities from Huanchaco, a fishing village located in the North Coast of Peru. Both celebrations are different in its origin but it roots are deeply buried in Prehispanic festivals and traditions. In this paper, I will describe in great detail these catholic festivities. Furthermore, I will argue that it is very possible that Spanish priest adapted traditional Roman Catholic celebrations with Prehispanic festivities in order to overlap both religious traditions.